Značilnosti publiciranja na področju gozdno-lesne verige in njihov vpliv na vrednotenje področij v sklopu evalvacij raziskovalnih dosežkov - pregled objav - Peteh, Maja (Acta silvae et ligni, 2016)
This article presents an overview of bibliometric research in the scientific fields of forestry, wood and paper sciences and highlights the characteristics of publishing in these areas, particularly those that affect the results of the evaluation process and, consequently, the development of these fields. Articles published in scholarly journals are considered important for the development of the scientific field and professional terminology, therefore the review focuses mainly on the specifics in the area of scientific publishing. Although forestry, wood and paper science comprise a single wood value chain, publications mainly cover only the forestry as a result of the interdisciplinary areas, different science classification schemes, narrow research areas, their role in the society. Research work under study focuses mainly on the publications indexed by citation databases WoS and Scopus. Some studies also present the findings on the level of individual institutions or countries. Publication of scientific papers in the field of forestry has an important impact on further development and continuation of journals in this field; especially in less common languages. An important part of articles in these fields is published in the journals which are not classified as forestry-associated indicating interdisciplinarity of the fields, cooperation between authors from different areas, as well as the impact of the evaluation policy on publishing patterns.
Keywords: bibliometrics; bibliometrija; forestry; gozdarstvo; lesarstvo; wood technology; paper technology; papirništvo; raziskovalna politika; research policy; vrednotenje raziskovalnih dosežkov